JUVENILE STAGES OF A FILE-FISH ASSIGNED TO PARAMONACANTHUS CHOIROCEPHALVS (BLEEKER) - Pillai, P K Mahadevan (Indian Journal of Fisheries, 2011)
A brief description of two juvenile stages of a file-flsh is given. A close study of their fin ray counts and the arrangement of spinnules on the dorsal spine revealed their nearness to Paramonacanthus choirocephalus (Bleeker). Similarities exhibited by these spjcimens to other allied species are discussed.